2018
DOI: 10.2116/analsci.18p369
|View full text |Cite
|
Sign up to set email alerts
|

An Ionic Liquid-based Microextraction Method for Ultra-High Preconcentration of Paraquat Traces in Water Samples Prior to HPLC Determination

Abstract: An ionic liquid (IL)-based microextraction method was developed for the preconcentration of paraquat traces in water samples prior to HPLC determination. On the basis of the relationship between the aqueous solubility and the extractability of known ILs, 1-ethyl-3-methylimidazolium bis(nonafluorobutanesulfonyl)amide ([EMIm][NNf2]) was selected as the extractant for paraquat. The distribution ratio of paraquat dication in the [EMIm][NNf2]/water biphasic system was theoretically estimated to be nearly 10 8 at it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…In LPME very low amount of toxic organic solvents was used during the extraction process [108][109][110][111]. Currently, the LPME pays more attention to green solvents like ionic liquids [112] and SUPRASs to minimize the use of toxic organic solvents during the extraction of targeted analytes. Due to its unique properties, SUPRASs have been used in the extraction field.…”
Section: Suprass-based Lpmementioning
confidence: 99%
“…In LPME very low amount of toxic organic solvents was used during the extraction process [108][109][110][111]. Currently, the LPME pays more attention to green solvents like ionic liquids [112] and SUPRASs to minimize the use of toxic organic solvents during the extraction of targeted analytes. Due to its unique properties, SUPRASs have been used in the extraction field.…”
Section: Suprass-based Lpmementioning
confidence: 99%
“…[18][19][20][21] However, the commonly used paraquat doses in animal models are too high and they do not represent the dosage rural residents and workers are exposed to. 22 In this context, it is suggested that there are triggering factors like systemic inflammatory diseases that may enhance the paraquat neurotoxicity. 16 Periodontal disease is considered the second most prevalent oral disease, reaching rates of 47.2% in adults and up to 70.1% in elderly.…”
Section: Introductionmentioning
confidence: 99%
“…18 21 However, the commonly used paraquat doses in animal models are too high and they do not represent the dosage rural residents and workers are exposed to. 22…”
Section: Introductionmentioning
confidence: 99%
“…The important features of LPME are the use of a small volume of extraction solvent, rapid process, and high enrichment factor [26][27][28][29]. Recently, LPME has been focused on green solvents, such as ionic liquid [30], to eliminate the use of toxic solvents.…”
Section: Introductionmentioning
confidence: 99%